Educate your children: The history of racialization in technological professional education” (1930/1950) in Pelotas/RS - Pinto, Natália Garcia (2023)
Interest in the discussion of racial relations between white and black subjects has been gaining ground in several areas in Brazilian society since the late 1990s. In the field of the history of education, there has been a lot of research on the racial diversity of school groups, the discussion of affirmative action in higher education, debates on whether to rethink the school as a producer or reproducer of mechanisms of social and racial inequalities. It is concluded, through the research carried out, by the images of the graduation boards, we understand that access to professional school was the element of cohesion and power maintenance of the local and national white elite. That is, even if in the investigated period, blacks had the right to have access to a professional education, their presence, which is minimal, indicates that it was prohibited through discrimination or mechanisms that made it difficult for them to remain in this school and professionalizing space.